A Celebrity from the Sky: ʿAbd al-Bāsiṭ ʿAbd al-Ṣamad’s Journey to National and International Fame in ʿAbd al-Nāṣir’s and al-Sādāt’s Egypt - Sayfo, Omar (Die Welt des Islams, 2022)
ʿAbd al-Bāsiṭ ʿAbd al-Ṣamad (1927–88) is one of the most renowned Egyptian Qurʾān reciters of the mujawwad and murattal styles, admired nationally and internationally for his remarkable voice and improvisatory style. Starting from the 1950s, his national and international career was entwined with the emergence of Egyptian mass media, which contributed not only to the spread of his voice on the radio, followed by the distribution of cassettes, but also to the formation of his image through a variety of media texts. While avoiding explicit political engagement, he largely contributed to the religious legitimation of ʿAbd al-Nāṣir’s and al-Sādāt’s policies by his presence at iconic events, as well as to the growth of Egyptian soft power. This article sets ʿAbd al-Bāsiṭ ʿAbd al-Ṣamad’s career within the media and political landscape of his time, exploring his journey from his Upper Egyptian home village to transnational celebrity.